Study on proppant migration and placement under sand-carrying action of clean fracturing fluid - ZUO Weiqin; XIE Kunrong; HAN Hongkai; LIU Yanwei; ZHAO Fajun; WANG Yang (Meikuang Anquan, 2022)
In order to explore the law of proppant migration and placement under clean fracturing fluid, an Euler multiphase flow model was established through FLUENT numerical simulation software based on computational fluid dynamics(CFD). The model takes into account the rheological properties of fracturing fluid and the friction and collision of proppant particles. The influence of proppant size, density and sand ratio on the shape of the sand dike is studied by using the equilibrium height and equilibrium time as the characterization parameters. The results show that the clean fracturing fluid is easier to carry the proppant to the depth of the fracture than the conventional fracturing fluid, so that the proppant is evenly distributed in the fracture; proppant with large particle size and high density can easily settle in the fracture opening under the carrying of the clean fracturing fluid, while proppant with small particle size and low density can improve the sand carrying capacity of fracturing fluid and transport proppant into deep fracture. Increasing sand ratio in a certain range can improve the height and laying area of the sand dike, but excessive sand ratio has little effect on the shape of the proppant sand dike and is easy to cause sand blockage.